Effects of Chamber Width on H2/Air Rotating Detonations - Hailong Zhang; Weidong Liu; Lin Zhang; Shijie Liu; Luxin Jiang (International Journal of Aerospace Engineering)
To get the effects of chamber width on the H2/Air rotating detonations, several models with different widths have been investigated. By using a one-step chemical reaction model, one wave is induced in all models. The chamber width has a significant effect on the flow field. When the chamber width is small, the variation of the flow field with the radius is not obvious. But when the width increases, the curvature of the detonation wave reflecting between the inner and outer walls at the head would become enlarged. The height of the detonation wave both on the inner wall and the outer wall has been presented. When the width reaches a limited value, the detonation wave cannot sustain on the inner wall. The normal velocity is used to characterize the detonation wave. The normal velocities on the outer wall and average diameter are almost the same. The former one is approximately the CJ value.